Altered expression of glycoproteins on the cell surface of Jurkat cells during etoposide-induced apoptosis: Shedding and intracellular translocation of glycoproteins - Sato, Hirotaka; Azuma, Yutaro; Higai, Koji; Matsumoto, Kojiro (Biochimica et biophysica acta, 2009)
The glycoproteins on the cell surface are altered during apoptosis and play an important role in phagocytic clearance of apoptotic cells. We classified Jurkat cells treated with etoposide as viable and early apoptotic cells, late apoptotic cells or secondary necrotic cells based on propidium iodide staining and scattered grams and estimated the expression levels of glycoproteins on the cell surface. The cell surface expression levels of intercellular adhesion molecules (ICAM)-2 and -3 on the apoptotic cells were markedly lower, while those of calnexin, calreticulin, and lysosome-associated membrane proteins (LAMP)-1 and -2 were significantly higher compared to non-apoptotic cells. These decreases in ICAM-2 and -3 on the apoptotic cell surface were reduced in the presence of metalloproteinase inhibitors and caspase inhibitors, respectively. Confocal microscopic analysis revealed that calnexin and calreticulin were assembled around fragmented nuclei of blebbed apoptotic cells. These results suggest that alteration of glycoproteins on the cell surface during apoptosis is associated with shedding and intracellular translocation of glycoproteins.